Criminal defense in China: the politics of lawyers at work - Liu, Sida (Cambridge studies in law and society, 2016)
"Illiberal political societies come with varieties of labels - absolute monarchies, military dictatorships, authoritarian or totalitarian politics, Big Man regimes, or dual states. Yet they share key features in common - little or no restraint on arbitrary executive power, most especially as it is exercised through military, police and security apparatuses; law that is distorted and circumscribed and ultimately ineffectual in its protections of individuals and organizations offensive to the ruling power; little space for voices to speak freely about their rulers, their qualities of life, or their circumstances in times and places and organizations of their own choosing; severely constricted notions of rights-bearing citizens beyond those granted or withdrawn by the rulers themselves; and precariousness of property ownership, among others"--